تأثير إضافة حمأة الصرف الصحي على التربة الكلسية من الأزوت الكلي والفوسفور المتاح وعلى الإنتاج الحبي لنبات الذرة البيضاء في منطقة المخرم (شرق محافظة حمص) - هيفا سوسن; العبدو عبد الإله; خنسه أسامه (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير إضافة مستويات مختلفة من حمأة الصرف الصحي على محتوى التربة الكلسية من الآزوت الكلي والفوسفور المتاح وعلى الإنتاج الحبي لنبات الذرة البيضاء في منطقة المخرم ( شرق محافظة حمص). نفذت التجربة في حقل تربة كلسية في قرية أبو العلايا من منطقة المخرم، فقد تمت دراسة تأثير إضافة معدلات مختلفة من حمأة الصرف الصحي Sewage Sludge (11 – 22 – 44- & 66 ) طن/ هكتار.أشارت النتائج إلى زيادة واضحة في التربة من الأزوت الكلي والفوسفور المتاح، وهذا يبين أهمية إضافة الحمأة إلى التربة الكلسية مما يساهم في إغناء التربة من هذين العنصرين، أيضاً أشارت النتائج إلى زيادة واضحة في إنتاجية نبات الذرة البيضاء مع ازدياد المستوى المضاف من الحمأة. The objective of this research was to study the effect of applying different levels of sewage sludge on Total Nitrogen and Available Phosphorus in the calcareous soil and the productivity of the Sorghumplantgrain in the AL-mukharam region(east of Homs governorate) Experiment was carried out in a calcareous soil field in the village of Abu Alallaya in the AL-mukharam region, where the effect of adding different rates of Sewage Sludge (11 - 22 -44 - & 66 tons / ha) had been examined. The results showed a significant increase in Total Nitrogen and Available Phosphorus of thesoil, and this shows the importance of adding Sludge to the calcareous soil, which in turn improves the soil content of those two elements. The results also showed that there is a significant increase in the productivity of the Sorghumplant when the added level of sludge increases.